CHARACTERISTICS OF COMBINED USE OF MEXICOR TOGETHER WITH SOME ANTIARRHYTHMIC DRUGS IN ACUTE OCCLUSION OF CORONARY ARTERY IN EXPERIMENTAL STUDY - A. A. Kotljarov; L. N. Sernov (Российский кардиологический журнал)
The aim of the study was to assess the influence of intravenous administration of mexicor (7mg / kg) on electrophysiological, hemodynamic action and antiarrhythmic activity of nibentan (1 mg / kg), propranolol (1,4mg / kg) and verapamil (0,4mg / kg) in acute myocardial ischemia in experimental study. The cats were examined. Changes in automatism of sinus node, conductivity and myocardial reflex excitability were estimated. Levels of intraventricular and arterial pressure were determined, antiarrhythmic activity was analyzed. Preventive use of mexicor in combination with antiarrhythmic drugs in acute occlusion of coronary artery has not been followed by their influence abatement on electrophysiological parametres of heart. The tendency to enhancement of membrane-stabilizing action of studied medications by antioxidant was observed. Mexicor not only relief antiarrhythmic activity of nibentan and propranolol and enhance protective activity of verapamil in occlusive arrhythmias, but as antioxidant reduces cardiodepressive and hypertension effect of antiarrhythmic drugs in acute occlusion of coronary artery.